Safety aspects of rafting trips along the Dunajec River Gorge - Andrzej Ostrowski; Arkadiusz Stanula; Zbigniew Małodobry; Aleksander Sapiński (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Physical activity in mountainous areas can take on very different forms of tourism and sports. Usually, the most popular forms of tourist transport are discussed and analyzed in the literature on the subject - hiking, skiing, cycling. Rafting is less popular, because there are no rivers in the mountains on which there would be convenient, safe and appropriately developed areas. It should be borne in mind that on a mountain river there are large changes in the dynamics of water flow, numerous rock steps, stony obstacles, as well as the possibility of a sudden change in weather, which is why the risk of an accident during rafting is greater than on rivers in lowland areas. In Poland, the exception on a national scale is the Dunajec River Gorge in the Pieniny Mountains. Tourist traffic in this area, due to the extremely charming Dunajec Gorge, is large and constantly growing. It is also influenced by river conditions related to numerous bends, rapids and variable dynamics of the current. The above advantages encourage conducting numerous organized or individual rafting trips. Being on a floating unit and the resulting risk of drowning obliges the organizers to take numerous preventive measures.